Temperature dependence of susceptibility in the ferrielectric phase of ammonium sulphate - Enginer, Y; Salihoglu, S; Yurtseven, H (Physical Soc Republic China, 2003)
We have developed a mean field model for the paraelectric-ferrielectric phase transition in ammonium sulphate. In our model we assume that the quadrupolar. interactions are the dominant mechanism for this type of transition. The fit of our calculated susceptibility to the experimental data shows that the free energy, with a quadrupolar coupling term, can also adequately explain the observed behaviour of ammonium sulphate.
Keywords: Deuteron Magnetic Resonance; Ferroelectric Transition; (Nh4)2so4; Raman; Salts; Mode